WHO DECIDES THE CHAMPION AND WHAT THE DECISION ABOUT? - Ariyani, Luh Putu Sri; Supriyanto, Wahyu (International Conference on Cultural Studies; Vol 2 (2019): Proceedings International Conference on Cultural Studies, 2019)
A school library has a special character that differs from that of other library. It can be seen from its location within the school and is not an independent unit. This position causes many schools to pay less attention to the library. The library is only used as a complementary tool for schools and is only arranged when needed. The school seems reluctant to manage the library seriously. They argue they do not have financial capital in its management. But from the reluctance of schools to develop their libraries, there is always a school that is considered worthy represent Bali at the national level. The purpose of this paper is to explore who and what decide the success of high school library in Singaraja and what capitals are developed to be selected as representative of Bali at the competition of national level. Case study was held in two schools that win the predicate as the best three last years. The schools are SMAN 1 & 4 Singaraja and SMAN 4 Singaraja, Bali.  Final remarks highlight that become a champion in school library competition needs more than library building and big collections. There are several parties who helped determine whether or not a school library champion, including headmasters, school librarian, library-teacher, ICT-teacher, pupils, school commitee, alumni association, the municipal library authorities, the municipal education authorities. The school library activities include creating an aesthetically pleasing and practical environtment, providing access to all kind of resources and encouraging reading for pleasure.